The impact of mode 4 on trade in goods and services - Marion Jansen; Roberta Piermartini (World Trade Organization (WTO), 2004)
This paper estimates the impact of liberalization of temporary movements of individual service suppliers on trade in goods and services. In particular, the paper looks at the impact of the so-called forth mode to provide a service on trade in services under the other three modes: cross-border service supply (Mode 1), consumption abroad (Mode 2) and commercial presence abroad (Mode 3). Estimates are obtained using a gravity model of trade augmented for a measure of temporary movements of service suppliers. Estimates of the size of a country's Mode 4 trade in services are based on specific information regarding the number of temporary foreign workers occupied in the service sector and their estimated average earnings, thus overcoming the limitations of traditional measures of Mode 4 based on remittances or compensation for employees. We find a positive and significant effect of temporary movements of service providers on merchandise trade and services trade under Mode 1 and 3. No significant relationship is found between services trade under Mode 2 and Mode 4.
Keywords: F13; F23; F29; 330; Mode 4; trade negotiations; trade in services; FDI